Measurement and analysis of damping in hydropower units - Lundström, Mattias (2005)
Hydropower and nuclear power are the most important sources of energy in Sweden. Half of Sweden’s total energy production is produced in the hydropower plants along the Swedish rivers. The size of the hydropower units in these power plants varies. The biggest hydropower unit in Sweden, Harsprånget G5, has a rotating structure that weighs over 1000 ton and generates almost 500 MW. Hydropower units use the kinetic energy of the falling water and transform it to electrical energy. In a hydropower unit as big as the G5, approximately 500 m3 water passes through the turbine each second. The enormous flow of water through the turbine and the enormous mass of the rotating structure results in huge loads on the bearings that supports the rotating structure. The characteristics of generator bearings and the loads acting on it has been analysed in this thesis. A method to determine bearing data from measured loads and displacements in the generator bearing has been developed and evaluated. The loads are measured with a method that allows bearing loads to be measured without disassemble the bearing. Disturbances that affect these measurements has also been analysed. MATLAB were used for mathematical computation and analysis. Data measured at the hydropower units were analysed and some disturbances were found. Most of the measured data were affected by 50 and 100 Hz disturbances. To avoid the influence of these disturbances appropriate filters should be used. Some strange frequency characteristics were also found in the measurements performed with the inductive displacement sensors. The huge magnetic field that surrounds the hydropower unit probably affects the inductive displacement sensors. Inductive displacements sensor should therefore be avoided in displacement measurements near generators at hydropower units. It is possible to calculate the bearing data for the generator bearing if the displacements and loads in the generator bearing are measured correctly. The bearing data for the generator bearing is calculated in ...